Cold War on CNN, Part 22: Star Wars 1980-1988 (United Kingdom : Jeremy Isaacs Productions, 1998)
In 1981, Ronald Reagan -- a strident Cold Warrior -- enters the White House on a platform of "making America strong again." Convinced the United States is lagging in the arms race, Reagan increases defense spending and proposes a "Star Wars" anti-missile system -- alarming leaders in Moscow.
Keywords: United Kingdom